The gods must be crazy II [videorecording (DVD)] - N!xau; Farugia, Lena; Strydom, Hans, 1947-; Uys, Jamie (Columbia TriStar Home Entertainment, 2004)
In this sequel to "The gods must be crazy," Xixo the bushman again collides with the so-called civilized world when he embarks on a search for his children, who are accidental stowaways on a poacher's truck.